2009
DOI: 10.1097/acm.0b013e3181b17b3f
|View full text |Cite
|
Sign up to set email alerts
|

The Jefferson Scale of Physician Empathy: Preliminary Psychometrics and Group Comparisons in Italian Physicians

Abstract: Findings generally provide support for the construct validity and reliability of the Italian version of the JSPE. Further research is needed to determine whether the lack of statistically significant differences in empathy by gender and specialty is related to cultural peculiarities, the translation of the scale, or sampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
100
6
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(143 citation statements)
references
References 19 publications
24
100
6
8
Order By: Relevance
“…This is consistent with the previous studies in the U.S., Europe, and Japan, which have disclosed higher levels of empathy in female medical students compared to their male colleagues [18,26,27]. However, some studies have noted the insignificant influence of gender on the empathy of medical trainees and specialists [28]. There are multiple possibilities regarding the role of gender in empathy.…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with the previous studies in the U.S., Europe, and Japan, which have disclosed higher levels of empathy in female medical students compared to their male colleagues [18,26,27]. However, some studies have noted the insignificant influence of gender on the empathy of medical trainees and specialists [28]. There are multiple possibilities regarding the role of gender in empathy.…”
Section: Discussionsupporting
confidence: 81%
“…The current study also showed a similar finding, and female students scored significantly higher than male students. On the other hand, few studies have shown no gender difference in empathy (Di Lillo et al 2009;Shariat & Keikhavani 2010). We also sought the gender difference of empathy in the three factors of the scale and observed that the difference exists only in two of the three factors of JSE (i.e., perspective taking and compassionate care).…”
Section: Discussionmentioning
confidence: 99%
“…This three-factor structure has been replicated in several studies and on different groups of subjects. However, because of the nature of EFA, which allows every item to be loaded on any of the factors regardless of the theoretical possibility of the association, it is predictable to witness discrepancies across studies on items loaded on extracted factors (Sherman and Cramer 2005;Di Lillo et al 2009;Ward et al 2009;, and sometimes, even on the factors themselves (Kwon Hesieh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Se ha estudiado la empatía en estudiantes de medicina, odontología y enfermería en diferentes países (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Sin embargo, en América Latina son pocos y se remiten esencialmente a los estudiantes de Kinesiología, Medicina y Odontología (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionunclassified